Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1289/ehp9018
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter and Dementia Incidence in the Adult Changes in Thought Study

Abstract: Background: Air pollution may be associated with elevated dementia risk. Prior research has limitations that may affect reliability, and no studies have evaluated this question in a population-based cohort of men and women in the United States. Objectives: We evaluated the association between time-varying, 10-y average fine particulate matter ( ) exposure and hazard of all-cause dementia. An additional goal was to understand how to adequately control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 59 publications
3
29
1
Order By: Relevance
“…By this metric, the emission reduction efforts of the last 20 years have had tremendous success in improving air quality in the cities of the Northeast U.S. Recent studies have shown how the negative health impacts of PM 2.5 exposure can begin to manifest below this threshold of 15 μg/m 3 . For this reason, understanding the pathways toward continued decreases of aerosol mass on the hottest days remains important.…”
Section: Discussionmentioning
confidence: 99%
“…By this metric, the emission reduction efforts of the last 20 years have had tremendous success in improving air quality in the cities of the Northeast U.S. Recent studies have shown how the negative health impacts of PM 2.5 exposure can begin to manifest below this threshold of 15 μg/m 3 . For this reason, understanding the pathways toward continued decreases of aerosol mass on the hottest days remains important.…”
Section: Discussionmentioning
confidence: 99%
“…Since these reviews large cohorts have replicated positive associations between PM2.5 and incidence of all-cause dementia [56,57], including French cohort data utilizing robust clinical assessment to identify cases [58 ▪ ] (instead of commonly used population-level data approaches) and Swedish cohort research which has described the appreciable modifying effect of cerebrovascular disease [59 ▪ ] building on previous work [60]. A handful of studies assessed specific cognitive profiles [61], and of interest new data suggested a weak mediating role of depressive symptoms between NO 2 ,PM 2.5 and acceleration of decline in episodic memory [62].…”
Section: Epidemiological Associations Between Air Pollutants and Ment...mentioning
confidence: 99%
“…Several prior and recent observations noted the links between diesel exhaust (DE) and particulate matter smaller than 2.5 µm (PM 2.5 ) and ultrafine PM (particles smaller than 1 µm) and AD-associated dementia ( [30] , [42] ; Cacciottolo, 2017; Chen et al, [27] ; Grande et al, [47] ; Yuchi et al, [125] ). A study on a large population cohort found that development of dementia is higher in individuals living close to heavy traffic [26] and a recently published epidemiological study again noted that elevated long-term exposure to PM 2.5 is associated with increased risk of dementia [102] . In a preclinical study, exposure to urban nanosized PM for 225 h over 15 weeks increased cerebral Aβ deposition in female AD mice [14] .…”
Section: Introductionmentioning
confidence: 97%